Observations on some effects of L-triiodothyronine on carbohydrate and lipid metabolism in man - Stamp, T. C. B. (1969)
Fasting serum lipid levels and changes in plasma glucose, fatty acid non-esterified (Nefa), and blood pyruvate levels during intravenous glucose tolerance tests were measured in 13 normal subjects before and one, five, and 15 days after the administration of 1-triiodothyronine (T3) calculated as 6 μg/kg body weight. Significant increases in the mean basal metabolic rate and the mean fasting plasma Nefa level occurred within 10 to 17 hours of a single dose of T3, while a rise in the mean fasting plasma glucose concentration just failed to achieve significance. Fasting concentrations of blood pyruvate and serum triglyceride were unaffected. A significant fall in serum cholesterol levels was produced and lasted at least five days. All other indices returned to normal by five days. During intravenous glucose tolerance tests performed at intervals after T3 administration no change in plasma glucose levels from control values was seen. Mean plasma Nefa and blood pyruvate levels, however, were significantly raised above control values during the early stages of the test 10 to 17 hours after T3. The relationship between these findings and those observed in clinical thyrotoxicosis is discussed.